2007
DOI: 10.2466/pms.104.1.32-42
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Simultaneous Model Observation and Self-Modeling of Volleyball Skill Acquisition

Abstract: This study examined the effect of feedback with simultaneous skilled model observation and self-modeling on volleyball skill acquisition. 53 pupils 12 to 15 years old formed two experimental groups and one control group who followed an intervention program with 12 practice sessions for acquisition and retention of how to receive a ball. Groups received different types of feedback before and in the middle of each practice session. Reception performance outcome (score) and technique in every group were assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 22 publications
1
32
0
Order By: Relevance
“…This established the specificity of a perceptual blueprint formed during the observational period on subsequent physical practice. What emerges from these studies and others (Barzouka et al 2007;Bouquet et al 2007;Ferrari 1996;McCullagh et al 1989;Schmidt and Lee 2005) is the hypothesis that observation of movement sequences and physical rehearsal share common cognitive mechanisms, and training of this circuit by either means improves novel motor-skill learning.…”
Section: The Shaping Of Action By Perceptionmentioning
confidence: 85%
“…This established the specificity of a perceptual blueprint formed during the observational period on subsequent physical practice. What emerges from these studies and others (Barzouka et al 2007;Bouquet et al 2007;Ferrari 1996;McCullagh et al 1989;Schmidt and Lee 2005) is the hypothesis that observation of movement sequences and physical rehearsal share common cognitive mechanisms, and training of this circuit by either means improves novel motor-skill learning.…”
Section: The Shaping Of Action By Perceptionmentioning
confidence: 85%
“…T-test and 505 agility tests were used in order to assess agility and time was recorded with the use of photocells [13,14]. For the evaluation of passing skills, overhead passing test and forearm passing test were conducted [26,27]. Participants were fully familiarized with the testing procedure a week before the beginning of the training program and the best out of two trials was recorded for each test [28].…”
Section: Methodsmentioning
confidence: 99%
“…Boyer et al demonstrated that expert modeling and video feedback improved skill accuracy more rapidly than coaching alone for four female participants. Other studies investigating expert modeling and video feedback have included teaching volleyball (Barzouka et al, 2007) and swimming (Hazen et al, 1990). An intervention package of expert video modeling and feedback may be effective when applied to other sports where the accuracy of gross motor movements is vital to the execution of specific maneuvers.…”
mentioning
confidence: 99%